Perancangan Sistem Informasi Pendataan Siswa/I Madrasah Tsanawiyah Pada Yayasan Pesantren Nahdhatul Islam Mancang - Raheliya Ginting; Meiliyani Br. Ginting; Kiki Ardianti (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2022)
Advances in information technology, encourage many people to create new innovations to help humans get information quickly and easily. Information System Student data is one thing that is very important in the world of education, apart from accelerating information it also activates the work of employees. With the information system will make work faster. The rapid development of the website has penetrated in various aspects of life, for example in the fields of economy, entertainment, and other fields, including education.